No means no: Ermineskin’s resistance to reserve surrender, 1902-1921 - Irwin, Robert (My University, 2003)
The patent to a section of land in the middle of Ermineskin's reserve was held by the Hudson's Bay Company and eventually sold to farmers. When the Department of Indian Affairs became aware of the situation, they embarked on a campaign to have the Ermineskin people surrender the land. This paper exams the practices of the Department of Indian Affairs and the determined resistance of the Ermineskin people to shed light on land surrender and Aboriginal agency.
Keywords: Department of Indian Affairs; indigenous rights